2020
DOI: 10.3889/oamjms.2020.4315
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Activity of Alpha-lactalbumin in Chronic Unpredictable Stress Model in Swiss Albino Mice

Abstract: BACKGROUND: Major depressive disorder (MDD) is a leading cause for morbidity and mortality. Whey protein components are recently used as functional foods with health benefits. Alpha-lactalbumin (A-LA) is an important component of whey protein. It is a good source of the essential amino acids. OBJECTIVE: This study aimed to examine the possible antidepressant effect of whey protein against MDD induced by chronic unpredictable stress (CUS) in mice. MATERIALS AND METHODS: CUS model is used to induce d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…DSFS might reduce ROS generation by scavenging radicals, thereby attenuating the damage to serotoninergic neurons induced by MDA (39). A similar finding revealed that α-lactalbumin treatment decreased MDA levels and normalized GSH levels (40). More importantly, CUMS reduced 5-HT levels in the hippocampus, which were restored by chronic administration of DSFS and WPC.…”
Section: Discussionmentioning
confidence: 62%
“…DSFS might reduce ROS generation by scavenging radicals, thereby attenuating the damage to serotoninergic neurons induced by MDA (39). A similar finding revealed that α-lactalbumin treatment decreased MDA levels and normalized GSH levels (40). More importantly, CUMS reduced 5-HT levels in the hippocampus, which were restored by chronic administration of DSFS and WPC.…”
Section: Discussionmentioning
confidence: 62%